Cigarette smoking and male sex are independent and age concomitant risk factors for the development of ocular sarcoidosis in a New Orleans sarcoidosis population - Janot, Adam C.; Huscher, Dörte; Walker, McCall; Grewal, Harmonjot K.; Yu, Mary; Lammi, Matthew R.; Saketkoo, Lesley Ann (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2015)
Introduction: Sarcoidosis is a multi-organ system granulomatous disease of unknown origin with an incidence of 1-40/100,000. Though pulmonary manifestations are predominant, ocular sarcoidosis (OS) affects 25-50% of patients with sarcoidosis and can lead to blindness. Methods: A retrospective, single-center chart review of sarcoidosis cases investigated variables associated with the development of OS. Inclusion criteria were biopsy-proven sarcoidosis, disease duration greater than 1 year, documented smoking status on chart review and documentation of sarcoid-related eye disease. Multivariate analysis identified independent risk factors for OS. Results: Of 269 charts reviewed, 109 patients met inclusion criteria. The OS group had a significantly higher proportion of smokers (71.4%) than without OS (42.0%, p=0.027) with no difference (p=0.61) in median number of pack years. Male sex was significantly higher in the OS group (57.1% versus 26.1%, p=0.009). Median duration of sarcoidosis was higher in the OS group (10 versus 4 years, p=0.031). Multivariate regression identified tobacco exposure (OR=5.25, p=0.007, 95% CI 1.58-17.41), male sex (OR=7.48, p=0.002, 95% CI 2.15-26.01), and age (OR=1.114, p=0.002, 95% CI 1.04-1.19) as concomitant risk factors for the development of OS. Conclusion: To date, there are few dedicated investigations of risk factors for OS, especially smoking. This investigation identified male sex, age, and tobacco exposure as independent risk factors for OS. Though disease duration did not withstand regression analysis in this moderately sized group, age at chart review suggests screening for OS should not remit but rather intensify in aging patients with sarcoidosis. (Sarcoidosis Vasc Diffuse Lung Dis 2015; 32: 183-143)